PERAN GURU PAI DALAM MEMBIMBING SISWA MENGHADAPI PENGARUH NEGATIF MEDIA SOSIAL - Afdan; Ruslan; Nuryulia (STKIP Subang, 2026)
This study aims to analyze the role of Islamic Education (PAI) teachers in guiding students to face the negative impacts of social media in the digital era. The rapid development of social media platforms such as TikTok, Instagram, WhatsApp, and YouTube has significantly influenced students’ behavior, social interaction, and moral values. This research employs a library research method with a qualitative approach by collecting and analyzing relevant literature, including books, scientific journals, and previous studies related to social media influence and the role of PAI teachers in character education. The findings show that students tend to use social media excessively, which leads to decreased learning concentration, reduced direct social interaction, declining communication ethics, and increased imitation of negative online content. Furthermore, social media contributes to behavioral issues such as cyberbullying, misinformation spread, and lifestyle changes that are not aligned with moral and religious values. The study also reveals that PAI teachers play a strategic role as educators, mentors, and role models in shaping students’ character through moral guidance, religious values, and ethical digital behavior education. The results are supported by Social Learning Theory by Albert Bandura and Psychosocial Development Theory by Erik Erikson, which explain that adolescents are highly influenced by their environment and are in the stage of identity formation. Therefore, strengthening the role of PAI teachers is essential to help students use social media wisely and responsibly while maintaining moral and religious values in their daily lives.